Quality of medical services: problems, evaluation and regulation - Yerdavletova, Farida; Mukhambetov, Temirkhan (Business: Theory and Practice, 2015)
One of the most acute problems in the healthcare industry – the problem of the quality of medical services. In this area, there is no established definition of medical services or approaches to quality management. The aim of the article is to analyze the existing definitions of “quality of medical services,” as well as development approach to managing medical organization. At the same time the management of the medical organization should be focused on ensuring the quality as the most important criterion for the organization. Methodology of the study is based on analysis and grouping of existing definitions of medical services, the factorial approach to evaluating the quality and organization of the process approach to management of the medical organization. Noting the versatility and diversity concepts of quality of care the authors suggest grouping of direct and indirect factors affecting the quality of medical services. However, it is important, according to the authors, to move from functional management to management based on the process approach, which provides better control over the processes of customer service. Is given process model of quality management of health services and highlights the main groups of processes in the medical organization.